2021
DOI: 10.1101/2021.01.13.21249761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invasive Mould Disease in Fatal COVID-19: A Systematic Review of Autopsies

Abstract: BackgroundInvasive mould disease (IMD) – most commonly pulmonary aspergillosis - is reported to affect up to a third of critically ill COVID-19 patients. Most reported cases are diagnosed with probable/putative COVID-19 associated pulmonary aspergillosis (CAPA) based on a combination of non-specific clinical, radiographic, and mycological findings, but the clinical significance – and whether these cases represent true invasive disease – is unresolved.MethodsWe performed a systematic review of autopsy series of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 75 publications
2
18
0
1
Order By: Relevance
“…Autopsy studies show that IPA is among the most commonly missed diagnoses in ICU in‐patient deaths from any cause 55 . A systematic review of an autopsy series in decedents with COVID‐19 also revealed the presence of CAPA in 11.7%, comprising 54.5% of autopsy‐confirmed invasive mould infections 56 . One of the main caveats in the timely diagnosis of CAPA is the lack of specific clinical presentation and radiological signs of COVID‐19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies show that IPA is among the most commonly missed diagnoses in ICU in‐patient deaths from any cause 55 . A systematic review of an autopsy series in decedents with COVID‐19 also revealed the presence of CAPA in 11.7%, comprising 54.5% of autopsy‐confirmed invasive mould infections 56 . One of the main caveats in the timely diagnosis of CAPA is the lack of specific clinical presentation and radiological signs of COVID‐19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…in the airways reflects colonization and not invasive disease. A systematic review found that autopsy-proven invasive mould disease is an uncommon finding in patients dying with COVID-19, occurring in <2% of decedents reported in autopsy case series (19). Moreover, in some reported cases of probable CAPA, post-mortem examination failed to confirm the diagnosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of corticosteroids and other immunomodulators were infrequently reported in CAPA and non-CAPA patients, precluding meaningful comparison. The degree to which these therapies may increase risk of CAPA is unclear (19). Finally, we did not formally assess risk of bias, and it is possible that the design of some cohort studies resulted in bias towards over- or underdiagnosing CAPA.…”
Section: Limitationsmentioning
confidence: 99%
“…in patients with severe COVID-19 [ [9] , [10] , [11] , [12] , [13] , [14] ]. Furthermore, this contrasting view is supported by an autopsy series and a recent systematic review of an autopsy series showing that proven CAPA is uncommon (<3%) [ 10 , 15 ]. Moreover, a case series did not show a worse outcome in putative CAPA cases, even in the absence of antifungal therapy [ 2 ].…”
mentioning
confidence: 99%